ETUDE SUR QUELQUES EUMASTACIDES DLNDOMALAISIE ORTH ACRID - BOLIVAR PIELTAIN, C (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1946)
Exam of blood and organ smears of 88 birds, belonging to 59 genera and 68 spp, from the state of Chiapas, Mexico, revealed 7 spp parasitized by Haemoproteus, 6 by Leu-cocytozoon and 6 by Plasmodium Parasites similar to Aegyptianella pullorum were foun
AN ESC NAC CIENC BIOL
Keywords: ETUDE, QUELQUES EUMASTA CIDES, DLNDO MALAISIE ORTH ACRID; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL